2023
DOI: 10.1111/acel.13767
|View full text |Cite
|
Sign up to set email alerts
|

Senolytic drugs, dasatinib and quercetin, attenuate adipose tissue inflammation, and ameliorate metabolic function in old age

Abstract: Aging results in an elevated burden of senescent cells, senescence‐associated secretory phenotype (SASP), and tissue infiltration of immune cells contributing to chronic low‐grade inflammation and a host of age‐related diseases. Recent evidence suggests that the clearance of senescent cells alleviates chronic inflammation and its associated dysfunction and diseases. However, the effect of this intervention on metabolic function in old age remains poorly understood. Here, we demonstrate that dasatinib and querc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 60 publications
(128 reference statements)
2
34
0
Order By: Relevance
“…7 Physiological levels of cellular senescence are critical for many reasons (eg, cancer suppression 8 and optimal wound healing 9 ); however, excessive accumulation of senescent cells occurs in multiple tissues with aging. [10][11][12] This age-related buildup of senescent cells can induce tissue dysfunction, at least in part through the SASP, and may be involved in several age-related pathologies. 11,12 As such, cellular senescence may contribute to vascular oxidative stress, reduced NO bioavailability, adverse changes to the aortic ECM, and vascular dysfunction with aging.…”
mentioning
confidence: 99%
“…7 Physiological levels of cellular senescence are critical for many reasons (eg, cancer suppression 8 and optimal wound healing 9 ); however, excessive accumulation of senescent cells occurs in multiple tissues with aging. [10][11][12] This age-related buildup of senescent cells can induce tissue dysfunction, at least in part through the SASP, and may be involved in several age-related pathologies. 11,12 As such, cellular senescence may contribute to vascular oxidative stress, reduced NO bioavailability, adverse changes to the aortic ECM, and vascular dysfunction with aging.…”
mentioning
confidence: 99%
“…Moreover, several other studies conducting transcriptomic analysis have reported changes in these pathways in the context of aging 22 (reduced), cellular senescence 23,24 (enhanced), HP 25 (enhanced), and especially in the context of CR 18,2628 (enhanced), where it is highly foreseeable. Recently, the senolytic agents dasatinib and quercetin were shown to have similar effects on both inflammation and metabolism in adipose tissue, using targeted assays 29 .…”
Section: Resultsmentioning
confidence: 99%
“…Increasing senolytic drugs, such as dasatinib and quercetin, have recently been discovered to remove senescent cells in several age-related disorders. [209][210][211][212][213][214] Further studies are warranted to develop novel strategies for the prevention and treatment of PDAC in elderly patients.…”
Section: Discussionmentioning
confidence: 99%